Plant Genomics 2019 Volume II - You, Frank M. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Vols 1 and 2 contain 57 papers in the Special Issue of 'Plant Genomics 2009' and cover a wide range of topics, highlighting the significant progress that has been made in recent years in our understanding of the genetics and genomics of plants' growth, development, and stress responses. These studies provide valuable insights into the potential applications of genomic tools and technologies for crop improvement and sustainable agriculture, as well as fundamental questions about the evolution and function of plant genes and genomes.